Inhibition of Pathogen Adhesion by Bacterial Outer Membrane‐Coated Nanoparticles. Issue 33 (4th July 2019) - Zhang, Yue; Chen, Yijie; Lo, Christopher; Zhuang, Jia; Angsantikul, Pavimol; Zhang, Qiangzhe; Wei, Xiaoli; Zhou, Zhidong; Obonyo, Marygorret; Fang, Ronnie H.; Gao, Weiwei; Zhang, Liangfang
Abstract: Anti‐adhesion therapies interfere with the bacterial adhesion to the host and thus avoid direct disruption of bacterial cycles for killing, which may alleviate resistance development. Herein, an anti‐adhesion nanomedicine platform is made by wrapping synthetic polymeric cores with bacterial outer membranes. The resulting bacterium‐mimicking nanoparticles (denoted "OM‐NPs") compete with source bacteria for binding to the host. The "top‐down" fabrication of OM‐NPs avoids the identification of the adhesins and bypasses the design of agonists targeting these adhesins. In this study, OM‐NPs are made with the membrane of Helicobacter pylori and shown to bind with gastric epithelial cells (AGS cells). Treatment of AGS cells with OM‐NPs reduces H. pylori adhesion and such anti‐adhesion efficacy is dependent on OM‐NP concentration and its dosing sequence. Abstract : Nanoparticles coated with bacterial outer membranes (denoted "OM‐NPs") are reported as an anti‐adhesion nanomedicine that competes with source bacteria for binding sites and therefore inhibits bacterial adhesion to the host cells. Specifically, OM‐NPs prepared with Helicobacter pylori outer membrane were demonstrated to inhibit bacterial binding to the gastric epithelial cells and stomach tissues.